Teachers Encounter in Project Based Learning Context: Challenges and Strategies - Manik, Putu Galuh Nayayika; Utami, I G A Lokita Purnamika; Adnyayanti, Ni Luh Putu Era (STKIP AGAMA HINDU SINGARAJA, 2024)
Project Based Learning is a teaching method that teachers can use and can provide various benefits for students. Of course, in implementing the Project Based Learning method, teachers will be faced with challenges that will occur. To face this challenge, teachers must of course use relevant strategies. This research was conducted at one of the international schools in Gianyar, Bali, namely Pelangi School Bali. The classes taken were grades 1 and 2. The observation checklist was used to see what challenges and strategies teachers faced when implementing Project Based Learning. Researchers also conducted interviews with two teachers in each class to strengthen the observation checklist used.